DIMenGeComS in action: evaluating its effectiveness on Mendelian genetics education - Azriel P. Barrientos; Monera A. Salic-Hairulla; Sotero O. Malayao Jr.; Saddam C. Bazer; Joy B. Bagaloyos (Journal of Education and Learning (EduLearn), 2026)
The primary goal of this study is to improve the understanding of Mendelian genetics among Grade 8 students through the use of digital interactive Mendelian genetic comic stories (DIMenGeComS). This research contributes to the field of education by providing an innovative and engaging method to teach complex genetic concepts. Utilizing a sequential explanatory mixed-methods research design, this study involved pretests and posttests to measure the effectiveness of DIMenGeComS. The key findings indicate a significant improvement in the students’ comprehension of Mendelian genetics as specified by normalized gain scores in sections such as Linnaeus (0.57), and Sampaguita (0.69), all of which were medium to approaching high-class gain and had significant probabilities (p0.0001) less than 0.05 level of significance. These results suggest that DIMenGeComS can be a valuable tool in science education, offering the potential for further research into its application in other areas of the curriculum.